2019
DOI: 10.1590/1516-3180.2018.0272280119
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety among patients undergoing dialysis and kidney transplantation: a cross-sectional study

Abstract: Despite advancements in renal replacement therapies and increased survival, patients still face several physical, psychological and social limitations as consequences of chronic kidney disease and treatment complexity. 1,2 The daily struggle with end-stage renal disease symptoms and related comorbidities, along with the need to cope with psychosocial stressors, directly impacts patients' quality of life and mental health. 3,4 Depression and anxiety are considered to be the most common end-stage renal disease-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
3
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 45 publications
4
55
3
9
Order By: Relevance
“…Oyekçin et al [141], in their small study group, found that depression and anxiety were more prevalent in HD than PD and control, and that chronic dialysis disturbed body image and decreased sexual satisfaction. Other recent studies also found that HD patients were more depressed and anxious than patients after RT [142][143][144]. In contrast, Peng et al found no difference in HRQOL between HD and PD patients in a large comparative study in Taiwan [145], and in a similar study of a Taiwanese cohort by Mau et al, only the subscales evaluating bodily pain and social functioning significantly differed between HD and PD patients [146].…”
Section: Erectile Dysfunctionmentioning
confidence: 92%
“…Oyekçin et al [141], in their small study group, found that depression and anxiety were more prevalent in HD than PD and control, and that chronic dialysis disturbed body image and decreased sexual satisfaction. Other recent studies also found that HD patients were more depressed and anxious than patients after RT [142][143][144]. In contrast, Peng et al found no difference in HRQOL between HD and PD patients in a large comparative study in Taiwan [145], and in a similar study of a Taiwanese cohort by Mau et al, only the subscales evaluating bodily pain and social functioning significantly differed between HD and PD patients [146].…”
Section: Erectile Dysfunctionmentioning
confidence: 92%
“…Depression and anxiety are common in dialyzed patients [11][12][13][14]. The prevalence ranges from about 12 to 52% for anxiety and from about 23 to 42% for depression [15][16][17], among others depending on the assessment tools used. Depression and anxiety are both associated with impaired quality of life in dialyzed patients [18][19][20], and with worse health outcomes and increased mortality [21][22][23][24][25][26][27][28].…”
Section: Of 10mentioning
confidence: 99%
“…The presence of comorbidities, loss of vascular access, and poor quality of life are associated with anxiety symptoms among dialysis patients. Depression and anxiety are common conditions of patients who experience dehydration syndrome in dialysis patients rather than transplant patients, (de Brito et al, 2019). The respondents with no Arterio fistula shunt installed experience anxiety, considering that every HD process must be carried out by injection.…”
Section: 40 Discussionmentioning
confidence: 99%